2013
DOI: 10.1177/1531003513512372
|View full text |Cite
|
Sign up to set email alerts
|

Technique of Implantation and Bail-Out Maneuvers for Endovascular Fenestrated Repair of Juxtarenal Aortic Aneurysms

Abstract: Endovascular repair of complex aneurysms involving the visceral arteries has become a reality. Fenestrated endovascular aortic repair (FEVAR) has been used with increasing frequency to treat complex aortic aneurysms. The Zenith fenestrated stent-graft system (Cook Medical Inc, Brisbane, Australia) was approved for commercial use in the United States in April 2012, offering a custom-made design with up to 3 fenestrations to treat short-neck infrarenal and juxtarenal abdominal aortic aneurysms. Nevertheless, FEV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…This technique involves the gradual insertion of the stent-graft under fluoroscopic guidance, with the surgeon making rotational adjustments to maintain the correct orientation of the position markers. 23 This torque applied by the surgeon is in the direction opposite to the measured iliac torsion. However, if the operator inserts the device fully, notes the alignment of the fenestrations, and fully removes the device before adjusting the alignment (multiple insertion technique), the amount of rotation observed in the idealized models was substantially lower.…”
Section: Discussionmentioning
confidence: 99%
“…This technique involves the gradual insertion of the stent-graft under fluoroscopic guidance, with the surgeon making rotational adjustments to maintain the correct orientation of the position markers. 23 This torque applied by the surgeon is in the direction opposite to the measured iliac torsion. However, if the operator inserts the device fully, notes the alignment of the fenestrations, and fully removes the device before adjusting the alignment (multiple insertion technique), the amount of rotation observed in the idealized models was substantially lower.…”
Section: Discussionmentioning
confidence: 99%
“…BAT is a new technique and developed to deal with severe tortuosity (loops) of arteries in the arterial system during a transradial procedure. It is analogous to similar techniques used to manage difficult fenestrated endovascular grafts 7 or promote passage of catheter-extension type devices down to coronary arteries. 8 In this technique, the PCI balloon is placed across the tip of the catheter and inflated at a low pressure (4-6 atm) while half of the balloon is protruding beyond the catheter.…”
Section: Discussionmentioning
confidence: 99%
“…1 Even in the presence of a re-expanded true lumen and a thrombosed thoracic false lumen after thoracic endovascular aortic repair (TEVAR), there is a continued risk of aortic rupture and a need for additional procedures due to progression of the dissection, aneurysm degeneration, or malperfusion. [2][3][4][5] In 2016, Barbante et al 4 reported a case of relining with a fenestrated endograft (fEVAR) after the PETTICOAT (provisional extension to induce complete attachment) technique for TBAD, underlining the complexity of the procedure. In such challenging cases, planning is sometimes not sufficient to develop an optimal technique of implantation, and advanced endovascular skills are necessary to achieve best results.…”
Section: Introductionmentioning
confidence: 99%
“…1 Even in the presence of a re-expanded true lumen and a thrombosed thoracic false lumen after thoracic endovascular aortic repair (TEVAR), there is a continued risk of aortic rupture and a need for additional procedures due to progression of the dissection, aneurysm degeneration, or malperfusion. 25…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation